RETRACTED: Histone Methyltransferase SETD1A Induces Epithelial-Mesenchymal Transition to Promote Invasion and Metastasis Through Epigenetic Reprogramming of Snail in Gastric Cancer - Wu, Jugang; Chai, Hongjuan; Shan, Haiyan; Pan, Chunpeng; Xu, Xin; Dong, Wenpei; Yu, Jiwei; Gu, Yan (Frontiers in Cell and Developmental Biology, 2021)
Aberrant epigenetic modification induces oncogenes expression and promotes cancer development. The histone lysine methyltransferase SETD1A, which specifically methylates histone 3 lysine 4 (H3K4), is involved in tumor growth and metastasis, and its ectopic expression has been detected in aggressive malignancies. Our previous study had reported that SETD1A promoted gastric cancer (GC) proliferation and tumorigenesis. However, the function and molecular mechanisms of SETD1A in GC metastasis remain to be elucidated. In this study, we found that overexpression of SETD1A promoted GC migration and invasion, whereas knockdown of SETD1A suppressed GC migration and invasion in vitro. Moreover, knockdown of SETD1A suppressed GC epithelial-mesenchymal transition (EMT) by increasing the expression of epithelial marker E-cadherin, and decreasing the expression of mesenchymal markers, including N-cadherin, Fibronectin, Vimentin and α-smooth muscle actin (α-SMA). Mechanistically, knockdown of SETD1A reduced the EMT key transcriptional factor snail expression. SETD1A was recruited to the promoter of snail, where SETD1A could methylate H3K4. However, knockdown of SETD1A decreased the methylation of H3K4 on snail promoter. Furthermore, SETD1A could be a coactivator of snail to induce EMT genes expression. Rescue of snail restored SETD1A knockdown-induced GC migration and invasion inhibition. In addition, knockdown of SETD1A suppressed GC metastasis in vivo. In summary, our data revealed that SETD1A mediated EMT process and induced metastasis through epigenetic reprogramming of snail.